PERANCANGAN MESIN PELET IKAN UNTUK MENINGKATKAN PRODUKTIVITAS BUDIDAYA PERIKANAN - Nur Rohmat, Yusup; Ghozali, Muhamad; Haris, EMin; Endramawan, Tito (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2025)
Indramayu is the largest rice barn area in Java, so it contributes waste from the rice production process, but the waste processing process is less productive or there are very few enthusiasts. So there is a very big opportunity by utilizing waste which is more useful, namely by processing it into fish pellets which have a high price value compared to other processing methods. The design of the rice husk grinding machine uses a type 32 disk mill knife and a type 32 fish pellet printer that will print 3 mm pellets with a machine frame dimension of 849 x 597 x 918. The frame of this machine uses 40 x 40 x 1.35 mm hollow iron. The specifications of this fish machine consist of three main components, namely a husk refiner, a pellet dough mixer, and a fish pellet molder driven by a combustion engine with the motor power and speed used, namely a refiner power of 1.82 HP with a speed of 3600 rpm, a mixer power of 1.86 HP with a speed of 771.42 rpm, a molding power of 0.56 HP with a speed of 771.42 rpm. So the total power used for this machine is 5.5 HP or 4.1 kw. So it can be seen that the motor power is 5.5 HP < 7 HP, so a 7 HP drive motor can be used.